Clinico-epidemiological study of dengue cases in a tertiary care hospital, Guwahati, Assam, India - Bhardwaj, Lalit Mohan; Borthakur, Swapnav; Bhattacharyya, Prabhas Chandra (International Journal of Advances in Medicine, 2017)
Background: Dengue fever (DF) is a common mosquito borne disease caused by dengue virus and is transmitted by Aedes mosquito. It is one of the major public health problems in India. A large-scale outbreak of dengue fever occurred in 2016 involving several districts of Assam. Here we report our experience with Dengue cases. The present study was aimed to assess clinical and epidemiological aspects of dengue cases presenting in down town hospital, Guwahati, Assam. Methods: A record based retrospective study conducted in our centre. Total 880 fever cases, fulfilling WHO criteria for dengue suspicion were included in our study. Required data from the entire laboratory confirmed cases from 1st January to 31st December 2016 were collected from MRD (medical record department) and analysed. Epidemiological data were compared with previous year’s available data from 1st January to 31st December 2015. Results: The number of dengue cases in 2016 clearly outnumbered the dengue cases in past years. Most of the cases were in the age group 20-50 years with a male preponderance. The outbreak occurred during the months of August-November indicating increased vector transmission in the monsoon and post monsoon periods. Average days of hospital stay were 6 days. Conclusions: Measures can be taken both at personal and government level to reduce morbidity and mortality from dengue particularly during the monsoon period.